Visit to villages outside of Dodoma, Tanzania - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Visit to farmer villages outside of Dodoma, Tanzania. The area is very dry and rough, feeling the impact of an increasingly variable rain and temperature increases. Feel free to use. Photo: C. Schubert (CCAFS)